A cosmetic composition and its application, and a method for improving skin barrier function or repairing skin barrier function

By using compositions with chondanosylin and hydrolyzing collagen in cosmetics, the problem of improving and repairing the skin barrier function improvement and repair effect in existing technologies is solved, and the effect of remarkable skin barrier repair and function improvement effect is achieved.

CN115634171BActive Publication Date: 2025-01-28BLOOMAGE BIOTECHNOLOGY CORP LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211324671.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-01-28
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The existing chondroitin sulfate and collagen compositions have no significant effect in improving skin barrier function and repairing skin barriers, and there are lack of research and reports on insignificant skin care effects.

Method used

A cosmetic composition, which contains sulfate and hydrolyzed collagen. The mass ratio is 1: 1-3, the pH value is between 4.5-6.5, and the ion strength is less than 0.26mol/kg, which is used to improve and repair the skin barrier function.

Benefits of technology

The composition can significantly repair the damaged skin barrier and significantly improve the barrier function of the uninterrupted skin barrier. It measures its effect by reducing the deserted water decentralization (Tewl).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a composition for improving skin barrier function and its application. The composition comprises chondroitin sulfate and hydrolyzed collagen, wherein the mass ratio of chondroitin sulfate to hydrolyzed collagen is 1:1-3. The composition forms a film on the skin surface to promote the repair and improvement of the skin barrier. The composition is applied to the test area of ​​the subject, and the TEWL decreases significantly after 2 hours and 4 hours, indicating that the skin barrier function of the composition described in the present application is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cosmetics, and in particular to a composition capable of improving skin barrier function or repairing skin barrier function. Background Art

[0002] Over the past decade, compositions for improving and enhancing skin barrier function have been the research focus of the industry.

[0003] As a multifunctional natural biodegradable biopolymer, collagen has been widely used in many fields such as industry, food, medicine, and cosmetics. At present, high molecular weight collagen in the industry is mainly extracted from the skin, bones, and tendons of terrestrial mammals (pigs and cattle). And because this type of collagen is obtained by extracting raw gel from the connective tissue of animals, including bones, cartilage, skin, tendons, etc., it has excellent physical and chemical properties, such as strong hydrophilicity, jelly-forming ability, and high side chain gene reactivity. Due to these advantages, it is widely used in various fields, such as food, medicine, cosmetics, and printing industry. At the same time, it has a wide range of sources, low prices, and good biocompatibility.

[0004] Chondroitin sulfate is one of the components of the connective tissue matrix in the body. Its mechanism of action may be related to inhibiting phosphodiesterase activity, increasing cyclic adenosine monophosphate content and activating lipolytic enzymes. It can promote peripheral circulation and regulate cell growth. Chondroitin sulfate is a type of glycosaminoglycan, a polysaccharide composed of repeating disaccharide units formed by D-glucuronic acid and N-acetylgalactosamine linked by β-1,4-glycosidic bonds, and is sulfated at the C-4 or C-6 hydroxyl of N-acetylgalactosamine. Chondroitin sulfate is present in large quantities in animal cartilage.

[0005] In the existing combination of chondroitin sulfate and collagen, the two components form a multiple network space structure through intermolecular interaction forces (such as hydrogen bonds, hydrophobic associations, etc.), thereby forming a breathable bionic membrane on the skin surface. However, the film-forming effect and skin care effect are not significant. There is currently no research or report on the reasons for the insignificant skin care effect. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present application provides a cosmetic composition comprising chondroitin sulfate and hydrolyzed collagen. The composition can improve the skin barrier function and promote the repair and improvement of the skin barrier.

[0007] The specific technical solutions of this application are as follows:

[0008] 1. A cosmetic composition comprising chondroitin sulfate and hydrolyzed collagen, wherein the mass ratio of the chondroitin sulfate to the hydrolyzed collagen is 1:1-3.

[0009] 2. The composition according to item 1, wherein the pH value of the composition is greater than 4 and less than 7, preferably, the pH value is 4.5-6.5, and more preferably, the pH value is 4.5-6.0.

[0010] 3. The composition according to item 1 or 2, wherein the ionic strength of the composition is <0.26 mol / kg, preferably, the ionic strength is 0.001-0.2 mol / kg, more preferably, the ionic strength is 0.001-0.1 mol / kg.

[0011] 4. The composition according to any one of items 1 to 3, wherein, in terms of mass percentage in the composition, the chondroitin sulfate is 0.2-0.8%, and the hydrolyzed collagen is 0.2-2.4%.

[0012] 5. The composition according to any one of items 1 to 4, wherein the hydrolyzed collagen is hydrolyzed collagen of animal origin, preferably, the hydrolyzed collagen is type I collagen.

[0013] 6. The composition according to any one of items 1 to 5, wherein the composition further comprises cosmetically acceptable excipients and active ingredients.

[0014] 7. Use of the composition according to any one of items 1 to 6 for improving skin barrier function.

[0015] 8. Use of the composition according to any one of items 1 to 6 for repairing the skin barrier.

[0016] 9. A method for improving skin barrier function or repairing skin barrier function, comprising using the composition according to any one of claims 1 to 6.

[0017] Effects of the Invention

[0018] The composition of the present application can significantly repair damaged skin barriers and significantly improve the barrier function of undamaged skin barriers. DETAILED DESCRIPTION

[0019] The present application is described in detail below. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0020] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0021] The present application provides a cosmetic composition comprising chondroitin sulfate and hydrolyzed collagen, wherein the mass ratio of the chondroitin sulfate to the hydrolyzed collagen is 1:1-3.

[0022] In one or more embodiments, the mass ratio of chondroitin sulfate to hydrolyzed collagen (m 硫酸软骨素 :m 水解胶原 ) is 1:1, 1:2, 1:3, etc.

[0023] In some embodiments, the pH value of the composition is greater than 4 and less than 7, preferably, the pH value is 4.5-6.5, and more preferably, the pH value is 4.5-6.0.

[0024] In some embodiments, the ionic strength of the composition is less than 0.26 mol / kg, preferably, the ionic strength is 0.001-0.2 mol / kg, more preferably, the ionic strength is 0.001-0.1 mol / kg.

[0025] In one or more embodiments, the ionic strength of the composition can be 0.001 mol / kg, 0.002 mol / kg, 0.003 mol / kg, 0.004 mol / kg, 0.005 mol / kg, 0.006 mol / kg, 0.007 mol / kg, 0.008 mol / kg, 0.009 mol / kg, 0.01 mol / kg, 0.02 mol / kg, 0.03 mol / kg, 0.04 mol / kg, 0.05 mol / kg, 0.06 mol / kg, 0.07 mol / kg, 0.08 mol / kg, 0.09 mol / kg, 0.1 mol / kg, 0.2 mol / kg, 0.21 mol / kg, 0.22 mol / kg, 0.23 mol / kg, 0.24 mol / kg, 0.25 mol / kg, etc.

[0026] In the present application, there is no limitation on the method for determining the ionic strength in the composition, and the ionic strength can be determined by conventional determination methods in the art, for example, the method disclosed in US4716118A or the method disclosed in US5106752A.

[0027] In some embodiments, the composition can be adjusted in pH value and / or ionic strength by adding a regulator. The regulator includes but is not limited to a regulator containing a polybasic organic acid, which can be citric acid, phosphoric acid, phthalic acid, etc., for example, a mixture of citric acid and trisodium citrate, or a mixture of citric acid, trisodium citrate and sodium chloride.

[0028] The content of the regulator is not limited in this application and can be set according to the pH value and / or ionic strength required by the composition. For example, the content of citric acid can be 0.01-0.05%, the content of trisodium citrate can be 0.001-0.02%, and the content of sodium chloride can be 0.1-1%.

[0029] In some embodiments, the chondroitin sulfate is 0.2-0.8% and the hydrolyzed collagen is 0.2-2.4% by mass percentage in the composition. For example, the chondroitin sulfate can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc.; the hydrolyzed collagen can be 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, etc.

[0030] In some embodiments, the hydrolyzed collagen is an animal-derived hydrolyzed collagen, preferably, the hydrolyzed collagen is a hydrolyzed collagen derived from type I hydrolyzed collagen. This application does not limit the animal source of type I hydrolyzed collagen, and type I hydrolyzed collagen is mainly found in the skin, tendons, and bone tissue of animals. The hydrolyzed collagen in this application can be extracted using animal skin, tendons, or bone tissue as raw materials. For example, type I hydrolyzed collagen can be extracted using bovine Achilles tendon as raw material. This application does not impose any restrictions on the extraction method, and it can be extracted according to conventional methods in the art, such as alkaline hydrolysis.

[0031] In some embodiments, the weight average molecular weight of the chondroitin sulfate is 2.0w-5.0w Da. For example, the weight average molecular weight of the chondroitin sulfate can be 2w Da, 2.1w Da, 2.2w Da, 2.3w Da, 2.4w Da, 2.5w Da, 2.6w Da, 2.7w Da, 2.8w Da, 2.9w Da, 3.0w Da, 3.1w Da, 3.2w Da, 3.3w Da, 3.4w Da, 3.5w Da, 3.6w Da, 3.7w Da, 3.8w Da, 3.9w Da, 4.0w Da, 4.1w Da, 4.2w Da, 4.3w Da, 4.4w Da, 4.5w Da, 4.6w Da, 4.7w Da, 4.8w Da, 4.9w Da, 5.0w Da, etc.

[0032] In some embodiments, the weight average molecular weight of the hydrolyzed collagen is not limited in this application, and it can be a weight average molecular weight commonly used in the art, for example, the weight average molecular weight can be 5w-10w Da, for example, it can be 5w Da, 6w Da, 7w Da, 8w Da, 9w Da, 10w Da, etc.

[0033] In some embodiments, the composition further includes cosmetically acceptable excipients, active ingredients, etc. For excipients, for example, polyols such as butanediol, pentanediol, etc.; small molecule sugars such as trehalose, etc.; natural high molecular polymers such as xanthan gum, hyaluronic acid, polyglutamic acid, etc.; synthetic high molecules such as carbomer, acrylic acid polymers, etc.; water-soluble active substances such as urea, dextran, etc. For active ingredients, for example, coenzyme Q10, chitosan, tocopherol acetate, nicotinamide, adenosine, inositol and natural plant extracts, etc.

[0034] In the present application, there is no limitation on the preparation method of the composition, which can be prepared according to conventional methods in the art, for example, dissolving chondroitin sulfate and hydrolyzed collagen in a solvent such as water to obtain a solution, and adding a regulator to adjust the pH value of the solution to obtain the composition.

[0035] The present application also provides the use of the above-mentioned composition in improving the skin barrier function. The present application also provides the use of the above-mentioned composition in repairing the skin barrier.

[0036] The present application also provides a method for improving skin barrier function or repairing skin barrier function, which comprises using the above composition on undamaged skin or damaged skin.

[0037] This application is for non-therapeutic purposes when achieving the purpose of improving barrier function or repairing skin barrier function.

[0038] The transepidermal water loss (TEWL) used in this application is a common indicator reflecting the barrier function of the stratum corneum. If TEWL changes negatively, the skin barrier is strengthened; if TEWL changes positively, the skin barrier is weakened.

[0039] Example

[0040] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially. The raw material information used in the examples and comparative example 1 is shown in Table 1.

[0041] Table 1 Raw material information table used in the examples and comparative examples

[0042] Raw material name purity Manufacturer Chondroitin sulfate sodium (CS, molecular weight 2.4wDa) / BoLangFu (Hangzhou) Biotechnology Co., Ltd. Animal-derived hydrolyzed collagen type I (Col, 6-7w Da) Purity greater than 98% BoLangFu (Hangzhou) Biotechnology Co., Ltd. Citric acid monohydrate(CA) AR Sinopharm Chemical Reagent Co., Ltd. Trisodium Citrate Dihydrate (Citrate) AR Sinopharm Chemical Reagent Co., Ltd. Disodium hydrogen phosphate dodecahydrate AR Sinopharm Chemical Reagent Co., Ltd. Sodium dihydrogen phosphate dihydrate AR Sinopharm Chemical Reagent Co., Ltd. Sodium chloride AR Sinopharm Chemical Reagent Co., Ltd. Purac PH90 (90% L-lactic acid aqueous solution) 90% Pruk Netherlands

[0043] Example 1 Preparation of the composition

[0044] Sodium chondroitin sulfate (CS) and animal-derived type I hydrolyzed collagen (Col) were dissolved in water to obtain a solution, wherein the mass percentage of CS was 0.4%, the mass percentage of Col was 0.8%, 0.024% CA and 0.003% Citrate were added as regulators, the pH of the composition was 4.5, and the ionic strength was 0.01 mol / kg.

[0045] The ionic strength is measured by the method disclosed in US Pat. No. 4,716,118A or the method disclosed in US Pat. No. 5,106,752A.

[0046] The preparation methods of Examples 2-8 are the same as those of Example 1, wherein

[0047] In Example 2, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.03% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.001 mol / kg.

[0048] In Example 3, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.01% CA and 0.019% Citrate are added as regulators, the pH of the composition is 6.0, and the ionic strength is 0.01 mol / kg.

[0049] In Example 4, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.011% CA, 0.001% Citrate and 0.5% NaCl are added as regulators, the pH of the composition is 5.2, and the ionic strength is 0.10 mol / kg.

[0050] In Example 5, the mass percentage of CS is 0.2%, the mass percentage of Col is 0.4%, 0.03% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.001 mol / kg.

[0051] In Example 6, the mass percentage of CS is 0.6%, the mass percentage of Col is 1.2%, 0.03% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.002 mol / kg.

[0052] In Example 7, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.4%, 0.02% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.001 mol / kg.

[0053] In Example 8, the mass percentage of CS is 0.4%, the mass percentage of Col is 1.2%, 0.05% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.002 mol / kg.

[0054] Comparative Examples 1-9 are prepared in the same manner as Example 1, wherein

[0055] In Comparative Example 1, CS, Col and a regulator were not added, the pH of the composition was 7.0, and the ionic strength was 0 mol / kg.

[0056] In Comparative Example 2, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.121% CA and 0.015% Citrate are added as regulators, the pH of the composition is 3.5, and the ionic strength is 0.04 mol / kg.

[0057] In Comparative Example 3, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.053% CA and 0.006% Citrate are added as regulators, the pH of the composition is 4.0, and the ionic strength is 0.02 mol / kg.

[0058] In Comparative Example 4, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.032% of disodium hydrogen phosphate dodecahydrate and 0.001% of sodium dihydrogen phosphate dihydrate are added as regulators, the pH of the composition is 7.0, and the ionic strength is 0.01 mol / kg.

[0059] In Comparative Example 5, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.8%, 0.011% CA, 0.001% Citrate and 1.5% NaCl are added as regulators, the pH of the composition is 5.8, and the ionic strength is 0.26 mol / kg.

[0060] In Comparative Example 6, the mass percentage of CS is 0.1%, the mass percentage of Col is 0.2%, 0.03% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.001 mol / kg.

[0061] In Comparative Example 7, the mass percentage of CS is 1.0%, the mass percentage of Col is 2.0%, 0.03% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.08 mol / kg.

[0062] In Comparative Example 8, the mass percentage of CS is 0.4%, the mass percentage of Col is 0.2%, 0.02% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.001 mol / kg.

[0063] In Comparative Example 9, the mass percentage of CS is 0.4%, the mass percentage of Col is 1.6%, 0.07% CA and 0.001% Citrate are added as regulators, the pH of the composition is 5.5, and the ionic strength is 0.002 mol / kg.

[0064] The active ingredients, active ingredient mass ratios, pH values ​​and ionic strengths in Examples 1 to 8 and Comparative Examples 1 to 9 are shown in Table 2.

[0065] Table 2

[0066]

[0067]

[0068] Experimental Example 1 Effect on Undamaged Skin

[0069] (1) Skin barrier effect 2 hours after applying the composition of the example or comparative example

[0070] TWEL determination of skin application area

[0071] 1. Preparation

[0072] Before the experiment, the subjects were required to clean the inner forearms of both hands by wiping them clean with dry ordinary facial tissue.

[0073] 2. Determination

[0074] Adjust the instrument according to the instruction manual of CK's multifunctional skin measuring instrument.

[0075] After the blank group measurement before the sample is used, the product area and the control area are measured (the inner forearms of the subjects' hands should be marked with the measurement area, and the test area should be a square area of ​​at least 3cmx3cm). Each area is measured in parallel at least 3 times. First, measure the initial value of each test area (before the sample is used), and then add the test sample at the specified amount (7.5μg / cm 2 ) for a single application, and use a latex fingertip to evenly apply the sample to the test area. After a set time (2h), measure the TEWL values ​​of the test area and the control area. The test of the same subject must be completed by the same measurement personnel using the same instrument, and the measurement probe should be cleaned between two measurements.

[0076] 3. Subject selection and test site

[0077] The subjects were selected to be between 18 and 65 years old (except pregnant or lactating women), with the basic value of the forearm test area capacitance skin moisture meter between 15 and 45 (Corneometer Unit, CU). The subjects had no serious systemic diseases, no immunodeficiency or autoimmune diseases, no skin treatment, beauty treatment or other tests that may affect the results at the test site, no active allergic diseases, no highly sensitive constitution, no use of hormone drugs and immunosuppressants in the past month, and no other clinical trials at the test site currently or in the past three months.

[0078] The test area should not be used for 2-3 days before the test (cosmetics or topical medicines), and should not be exposed to water for 1h-3h. The test area should be marked on the inside of the forearms of both hands of the test subject. The test area should be at least 3cmx3cm square area. Multiple areas can be marked on the same arm at the same time, and each test area should be at least 1cm apart. Before the formal test, you should sit quietly in a constant temperature and humidity room at 22-23℃ and 40%-60% humidity for at least 20 minutes. You cannot drink water or beverages. Your forearms should be exposed and placed in the test state, and you should stay relaxed. The product application area and the blank control area should be randomly distributed in the marked areas of the left and right arms to ensure that all product and blank area positions are statistically balanced.

[0079] 4. Application method

[0080] Use a pipette (Eppendorf pipette) to accurately transfer the specified amount of test sample (7.5 mL / cm 2 ) for a single application and use a latex finger cot to evenly apply the sample to the test area.

[0081] 5. Number of measurements

[0082] Using a multifunctional skin measuring instrument (Courage+Khazaka TM HEX) test each smear area, and each area is measured at least 3 times in parallel

[0083] 6. Data processing

[0084] Descriptive statistics were performed on the measured values ​​of each test area, including quantity, mean, standard deviation, minimum value, median value and maximum value.

[0085] in:

[0086] The value of the TEWL test result of the test area P of the subject L is the arithmetic mean of the sum of its multiple measurement values ​​(at least 3 times), that is:

[0087] X LP0 =(X LP01 +X LP02 +...+X LP0K ) / K

[0088] X LP1 =(X LP11 +X LP12 +...+X LP1K ) / K

[0089] The average TEWL measurement value of area P of all subjects is the arithmetic mean of the sum of the TEWL measurement results of area P of each subject, that is:

[0090] X P0 =(X 1P0 +X 2P0 +...+X NP0 ) / N

[0091] X P1 =(X 1P1 +X 2P1 +...+X NP1 ) / N

[0092] The change rate of the average TEWL value of area P 2 hours after the subjects used the sample and before using the sample, that is,

[0093] Delta P=((X 1P1 -X1P0 )+(X 2P1 -X 2P0 )+...+(X NP1 -X NP0 )) / X P0

[0094] The formula is explained as follows:

[0095] N: number of testers

[0096] M: number of test points

[0097] K: Measurement test at the same test point (≥3)

[0098] X LP0 : Blank TEWL measurement of region P for subject L

[0099] X LP1 : TEWL measurement of area P of subject L 2 hours after smearing sample

[0100] X LPK0 : Blank TEWL measurement value X of the Kth repeated measurement of area P of the Lth subject LPK1 : TEWL measurement value of the Kth repeated measurement of area P of the Lth subject 2 hours after the smear sample

[0101] X P0 : Mean of blank TEWL measurements for area P of all subjects

[0102] X P1 : The average TEWL measurement of area P of all subjects 2 hours after applying the sample

[0103] Delta P: The change rate of the average TEWL value of area P 2 hours after the subject used the sample compared with that before using the sample

[0104] Statistical analysis was performed to analyze the differences between the product area and the blank control area at different time points. If the test data was normally distributed, the f test method was used for statistical analysis; if the test data was non-normally distributed, the rank sum test method was used for statistical analysis.

[0105] The statistical method used was a two-tailed test with a test level of a=0.05. The results are shown in Table 3.

[0106] Table 3 TEWL increment table of skin application sample area

[0107] serial number TEWL increase 2 hours after application Is it optimal? Example 1 -10.17% yes Example 2 -15.32% yes Example 3 -12.52% yes Example 4 -7.62% yes Example 5 -5.50% yes Example 6 -10.20% yes Example 7 -8.57% yes Example 8 -11.60% yes Comparative Example 1 1.41% no Comparative Example 2 2.5% (sample with precipitation) no Comparative Example 3 1.3% (sample with precipitation) no Comparative Example 4 2.2% (sample with precipitation) no Comparative Example 5 3.25% no Comparative Example 6 4.93% no Comparative Example 7 -0.71% (some subjects experienced irritation) no Comparative Example 8 0.73% no Comparative Example 9 -4.25% no

[0108] As can be seen from Table 3, after 2 hours of using the compositions of Examples 1-8, the increments of TEWL are all negative and their absolute values ​​are greater than 5%, indicating that the compositions of Examples 1-8 have a significant effect on improving the barrier function of the skin. The increments of TEWL using the compositions of Comparative Examples 1-6 and 8 are all positive, indicating that the compositions of Comparative Examples 1-6 and 8 weaken the barrier function of the skin. Although the increments of TEWL using the compositions of Comparative Examples 7 and 9 are negative, their absolute values ​​are less than 5%, indicating that the compositions of Comparative Examples 7 and 9 do not have a significant effect on improving the barrier function of the skin.

[0109] (2) Skin barrier effect after applying the composition of Examples 2 and 3 for 4 hours

[0110] The TEWL values ​​of the skin areas applied with the compositions of Examples 2-3 were tested before use and 4 hours after use according to the above test method. The results are shown in Table 4.

[0111] Table 4 TEWL increment table before and after application

[0112] serial number TEWL increase 4 hours after application Is it optimal? Example 2 -12.70% yes Example 3 -13.52% yes

[0113] It can be seen from Table 4 that 4 hours after using the compositions of Examples 2 and 3, the TEWL increment is negative and its absolute value is greater than 5%, indicating that the compositions of Examples 2 and 3 have a significant effect on improving the skin barrier function.

[0114] Experimental Example 2 Effect on damaged skin

[0115] Skin stimulation method (creating damaged skin): According to the lactic acid stimulation model commonly used in the cosmetics industry, a 10% lactic acid solution (wt%) was prepared using deionized water and lactic acid (brand name: Purac PH90) produced by the Netherlands Purac Company. A pipette (Eppendorf pipette) was used to accurately pipette the 10% lactic acid solution (dosage: 7.5 mL / cm 2 ) Apply the sample once on the selected area of ​​the skin, use a latex fingertip to evenly apply the sample to the skin test area, and after 2.5 minutes, wash the applied area with deionized water and wipe it clean with dry ordinary facial tissue.

[0116] Test method: Use a pipette (Eppendorf pipette) to accurately transfer the test sample (volume: 7.5mL / cm 2 ) Apply the sample once on the selected area of ​​the skin, use a latex fingertip to evenly apply the sample to the skin test area, sit still for at least 20 minutes, do not drink water or beverages, expose your forearm, place it in the test position, and keep relaxed.

[0117] Experimental groups:

[0118] Blank control group: 100% deionized water was directly applied to the selected area of ​​the skin;

[0119] Negative control group: first apply 10% lactic acid solution to the selected area of ​​the skin according to the above skin stimulation method, and then wash the applied area with deionized water;

[0120] Test group: firstly, 10% lactic acid solution was applied to the selected skin area according to the above skin stimulation method, and then the composition of Example 2 was tested according to the above test method.

[0121] The TEWL value of the selected skin area was tested before use and 2 hours after application according to the same TWEL measurement method as in Experimental Example 1. The results are shown in Table 5.

[0122] Table 5 TEWL increment table before use and 2h after application

[0123] sample TEWL increase 2 hours after application Is it optimal? Blank control group 1.41% NA Negative control group 5.38% NA Experimental Group -5.4% yes

[0124] As can be seen from Table 5, when the composition of Example 2 of the present application was applied to the damaged skin area, 2 hours after application, the TEWL increment was negative and its absolute value was greater than 5%, which shows that the composition of the present application has a significant effect on the skin barrier repair effect of damaged skin.

[0125] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. A cosmetic composition comprising chondroitin sulfate and hydrolyzed collagen, wherein the mass ratio of chondroitin sulfate to hydrolyzed collagen is 1:1-3; The chondroitin sulfate is 0.2-0.8% by mass in the composition; The pH value of the composition is 4.5-6.5; The ionic strength of the composition is ≤0.1 mol / kg; The hydrolyzed collagen is type I hydrolyzed collagen of animal origin.

2. The composition according to claim 1, wherein the pH value of the composition is 4.5-6.

0.

3. The composition according to claim 1, wherein The ionic strength of the composition is 0.001-0.1 mol / kg.

4. The composition according to claim 1, wherein Calculated by mass percentage in the composition, the hydrolyzed collagen is 0.2-2.4%.

5. The composition according to any one of claims 1 to 4, wherein The composition further comprises cosmetically acceptable auxiliary materials and active ingredients.

6. Use of the composition according to any one of claims 1 to 5 in preparing a product for improving skin barrier function.

7. Use of the composition according to any one of claims 1 to 5 in preparing a product for repairing skin barrier.

8. A non-therapeutic method for improving skin barrier function or repairing skin barrier function, the method comprising using the composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for determining ionic strength of a sample

    US4716118A

  • Method and reagent for determining the ionic strength or specific gravity of aqueous liquids

    US5106752A

  • Nutritional selenium-rich mask

    CN108245452A